Archaeological practice in Great Britain a heritage handbook - Schofield, John 1948-; Carman, John; Belford, Paul; SpringerLink (Online service). (New York Springer, 2011)
The heritage sector is now one of Britain's bigger industries, in terms of income generation and jobs (over 460,000 at the last count). It is also a popular industry to work in, attracting prospective employees from the home countries and from overseas. Yet, surprisingly, there is virtually no comprehensive overview from which to begin one's preparation. This manual intends to meet that need, telling readers a little about a lot, and thus complementing the many sources that provide further colour and detail. The Heritage Handbook is a unique ?user guide? to practicing archaeology and working in the cultural heritage sector within the diverse settings of Great Britain, comprising of: England, Scotland, Wales, the Isle of Man and the Channel Islands. The Heritage Handbook is different to other textbooks. Presented in an accessible style, with a comprehensive and up-to-date bibliography and lists of useful websites, this book is written specifically as a sourcebook for budding archaeologists and other heritage practitioners, while providing useful context and information for those working elsewhere in the heritage sector, away from the ?coalface?. The three main authors have very different but complementary backgrounds, and in writing this book they have taken responsibility for the topics they know best. Other professionals with particular areas of expertise contribute short sections on particular (and often practical) subjects such as health and safety. Throughout, the specific contexts and differences between the various component nations and regions of Great Britain will be made clear, as will the similarities
Archaeological Practice in Great Britain; Preface; Acknowledgements; Contents; List of Figures; List of Tables; 1. Introduction: archaeology in Great Britain 2. A history of archaeology in Britain 3. Britain's Archaeological Resource: a brief survey 4. Legal and administrative frameworks 5. Acquiring Data : before fieldwork 6. Acquiring Data: during excavation and survey 7. Achieving Results: analysis, application, publication and dissemination 8. Opportunities, Funding, and Keeping Safe Appendix: Useful websites Bibliography Index
Includes bibliographical references and index
Electronic reproduction
Keywords: Archaeology -- Great Britain -- Handbooks, manuals, etc